Use of assistive devices by individuals with hands osteoarthritis - Patrícia da Silva Santos (Cadernos Brasileiros de Terapia Ocupacional, 2018)
Introduction: Hands osteoarthritis is a joint disease that causes pain, stiffness, deformity, and loss of mobility. It has huge functional and negative impact on people’s quality of life by making the common daily activities difficult and painful. Assistive devices are strategies used by occupational therapists for the symptomatic treatment hands osteoarthritis. Objective: To identify and describe assistive devices indicated for individuals with hands osteoarthritis through an Occupational Therapy intervention. Method: A Cross-sectional study, conducted on subjects diagnosed with hands osteoarthritis in an Occupational Therapy clinic at a reference hospital in the state, from August to September 2015. Sixteen participants answered a researcher-developed semi-structured questionnaire, focusing on the description and frequency of use of specified assistive devices. Data were analyzed using descriptive statistics through a measure of central tendency and probability distribution. Results: The assistive devices used in the daily lives of the 16 individuals interviewed were: adapters for dressing, adapters for bathing, peelers, thickeners, jar/bottle openers, and cutters. were in the routine of individuals 84% of these assistive devices with a daily, weekly and monthly frequency. Conclusion: In this study, individuals suffering from hand osteoarthritis used adapters for dressing, adapters for bathing, thickeners, peelers, jar/bottle openers and cutters as assistive devices.